2013
DOI: 10.1186/1746-6148-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic variation and geographic distribution of porcine reproductive and respiratory syndrome virus on infectivity and pig growth

Abstract: BackgroundThe porcine reproductive and respiratory syndrome (PRRS) is a devastating disease for the pig industry. In this study, we analysed the genetic variability of PRRS virus (PRRSV) as well as the relationship between the genetic variability, the geographical and temporal distribution of the PRRSV strains. Moreover, we investigated the association between the glycosylation patterns in PRRSV sequences and pigs growth.ResultsThe data highlight that PRRSV strains evolve rapidly on individual farms, and tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
2
1
Order By: Relevance
“…Contrary from what was previously reported in literature (Wissink et al, 2004), the presence of several strains collected at different points in time without N-46 confirms that this glycosylation is not essential for viral infectivity, a phenomenon recently reported for Type 2 (Wei et al, 2012). However, the high prevalence of this glycosylation site suggests that it could influence susceptibility to pig immune response (Ansari et al, 2006;Vu et al, 2011) and may consequently have repercussions on pigs' performance (Badaoui et al, 2013). Accordingly, the extremely limited number of strains lacking glycosylation in positions 35-37 and 53 could be due to an earlier and higher induction of neutralizing antibodies by strains devoid of these glycosylation sites, as reported by Faaberg et al (2006).…”
Section: Discussioncontrasting
confidence: 81%
“…Contrary from what was previously reported in literature (Wissink et al, 2004), the presence of several strains collected at different points in time without N-46 confirms that this glycosylation is not essential for viral infectivity, a phenomenon recently reported for Type 2 (Wei et al, 2012). However, the high prevalence of this glycosylation site suggests that it could influence susceptibility to pig immune response (Ansari et al, 2006;Vu et al, 2011) and may consequently have repercussions on pigs' performance (Badaoui et al, 2013). Accordingly, the extremely limited number of strains lacking glycosylation in positions 35-37 and 53 could be due to an earlier and higher induction of neutralizing antibodies by strains devoid of these glycosylation sites, as reported by Faaberg et al (2006).…”
Section: Discussioncontrasting
confidence: 81%
“…The lack of a strong spatial component that would be indicative of local spread is in agreement with previous studies (Goldberg et al., ; Badaoui et al., ; Rosendal et al., ) and in contrast to several findings from other source populations (Mondaca‐Fernandez et al., ; Otake et al., ; Lambert et al., ). It is interesting to note that most statistically significant associations were detected for PRRSV 1‐8‐4.…”
Section: Discussionsupporting
confidence: 92%
“…While some previous studies have also found that airborne transmission of PRRSV as an important route of viral spread [ 7 , 9 ] others have suggested that the relevant route of spread is animal movement, based on molecular epidemiology [ 30 , 31 , 32 ]. In theory, if the only route of PRRS spread were airborne, an association between the space and genetic variation would be expected, but because the virus is spread by animal movement, as well as air, evidence of this association is difficult to assess.…”
Section: Discussionmentioning
confidence: 99%